A gel base and a composite tissue filler, a preparation method thereof, and application thereof in tissue filling

CN122874643APending Publication Date: 2026-10-09XIAN RUNYU MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611264940.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

此外,现有技术通过将ECM或者dECM进行酶水解得到溶液,再与凝胶基质物理混合或者交联来解决悬浮问题,但此方法的成本偏高

Benefits of technology

本申请提供的凝胶基质,是一种结合透明质酸或其盐、聚谷氨酸或其盐和琼脂糖各自特点形成的物理交联凝胶,其避免了化学交联剂的使用,既能悬浮一定脱细胞真皮基质等生物活性材料,又能在悬浮状态下顺利注射不堵针,且缓慢降解的产品。其中,物理交联是指通过物理作用力,如静电作用、离子相互作用、氢键作用、链的缠绕等形成凝胶,避免化学交联剂的使用,本申请所采用的物理交联方式,主要利用琼脂糖、聚谷氨酸或其盐和透明质酸或其盐3种高分子之间的静电相互作用及氢键作用形成物理交联凝胶。透明质酸凝胶作为半刚性结构和聚谷氨酸的柔性结构可解决琼脂糖的脆性大、质地生硬,注射术后干燥等问题,同时透明质酸和聚谷氨酸复合可提高复合凝胶的保湿性能,抑制透明质酸的降解,延长降解时间。相较于对比例1.1、1.2和1.3,本申请提供的凝胶基质既具有缓慢降解的性能,又具备一定悬浮能力,不使用交联剂,且具有良好的注射性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of medical biomaterials, and particularly relates to a gel matrix and a preparation method thereof, a composite tissue filler and a preparation method thereof, and application of the gel matrix and the composite tissue filler in tissue filling. The gel matrix comprises hyaluronic acid or a salt thereof, polyglutamic acid or a salt thereof and agarose, wherein the hyaluronic acid or the salt thereof, the polyglutamic acid or the salt thereof and the agarose are crosslinked to form a gel; the composite tissue filler comprises a bioactive material and the gel matrix; the gel matrix has slow degradation performance and certain suspension capacity, does not use a crosslinking agent, and has good injection performance; and the filler can slowly degrade, does not use a crosslinking agent, and can provide good injection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of medical biomaterials, specifically to a gel matrix and its preparation method, a composite tissue filler and its preparation method, and the application of the gel matrix and the composite tissue filler in tissue filling. Background Technology

[0002] As we age, the skin gradually loses collagen, hyaluronic acid, and adipose tissue, causing the once full facial contours to become increasingly gaunt and various wrinkles to appear. Prolonged sun exposure is the primary external factor accelerating this process, and years of repetitive facial expressions cause the skin to fold continuously, gradually forming static wrinkles in areas such as the forehead, between the eyebrows, nasolabial folds, around the mouth, and around the eyes. One of the most direct and effective rejuvenation methods for addressing these wrinkles is injectable fillers. With further research, the mechanism of action of injectable fillers has gradually expanded from early physical filling to stimulating collagen regeneration and even biologically targeted regeneration. Currently, mainstream sodium hyaluronate fillers still carry the potential risks of cross-linking agents, such as 1,4-butanediol diglycidyl ether (BDDE) and its hydrolysis product, 1,4-butanediol di-(propane-2,3-diol) ether (BDPE). Combined with their swelling properties, this can lead to facial "swelling" in the later stages of injection (Wang Zhipeng, Research on the Repair and Treatment of Swelling and Other Complications Caused by Facial Injection Hyaluronic Acid [J]. Medical Aesthetics and Cosmetology, 2023, 32 (23): 197-200). Collagen fillers generally have a higher risk of allergic reactions than sodium hyaluronate fillers. Commercially available collagen stimulating and regenerating agents, such as microspheres, rely on the synergistic effect of the microspheres and their matrix to achieve filling. However, most existing products use uncross-linked gel matrices, which degrade too quickly after implantation, resulting in insufficient short-term support. Even when cross-linked matrices are used, the risk of residual cross-linking agents and their hydrolysis products remains. Tissue fillers are developing along the path of "physical filling → stimulation of regeneration → targeted regeneration". Targeted regeneration of bioactive materials, represented by extracellular matrix (ECM), has become a key direction for the development of tissue fillers.

[0003] Extracellular matrix (ECM) is a large molecular complex secreted by cells, mainly composed of collagen, elastin, glycosaminoglycans (such as hyaluronic acid), and growth factors. It not only provides physical support for cells but also directionally regulates cell proliferation, differentiation, and tissue regeneration. Decellularized extracellular matrix (dECM) is a matrix material obtained by removing cellular components from ECM through a decellularization process. This process significantly reduces the immunogenicity and rejection risk of ECM while preserving its natural three-dimensional structure and bioactivity. Acellular dermal matrix (ADM) is a type of dECM that can remain in vivo for at least one year without cross-linking, making it an excellent natural support material for facial fillers. However, when expanding its applications, it was found that when ADM is pulverized into particles to obtain micronized acellular dermal matrix (mADM), stratification and sedimentation occur when mixed with water, rendering it unusable. Furthermore, before injection, it presents as solid aggregates of particles, posing problems such as needle clogging. To improve the stratification and sedimentation phenomenon, researchers have attempted to add substances such as hyaluronic acid and collagen, utilizing their unique viscosity to act as a suspending agent. However, in practical applications, it has been found that even with the addition of suspending agents, stratification and sedimentation still occur during transportation or under irradiation conditions. Patent CN116212112 A (Patent Title: An Injectable Filler Material and Its Preparation and Application) mentions that hyaluronic acid alone lacks sufficient suspending capacity, leading to an inability to stabilize the gel. Gel stabilization is achieved by selecting sodium hyaluronate with a specific molecular weight and specific irradiation parameters. Furthermore, existing technologies address the suspension problem by enzymatically hydrolyzing ECM or dECM to obtain a solution, which is then physically mixed or cross-linked with the gel matrix; however, this method is costly.

[0004] Agarose is a natural linear polysaccharide derived from red algae. Its basic repeating units consist of β-D-galactose and 3,6-dehydro-α-L-galactose, exhibiting good biocompatibility and no immunogenicity. This material is temperature-sensitive, melting upon heating and forming a gel upon cooling. In the gel state, the molecular chains exist in a double helix conformation and further aggregate to form a three-dimensional network structure. Agarose can construct an ECM-like three-dimensional network of porous microstructures, providing a suitable microenvironment for cell growth and proliferation. Due to these unique properties, agarose shows broad application prospects in the field of dermatology.

[0005] Polyglutamic acid (γ-PGA) is a water-soluble polyamino acid, typically produced by fermentation with Bacillus subtilis. Its molecular chain consists of glutamic acid units linked by peptide bonds between α-amino and γ-carboxyl groups. Due to the presence of highly reactive carboxyl groups in its side chains, γ-PGA readily reacts with other substances to form stable complexes and possesses extremely strong hydrophilicity, with moisturizing properties even surpassing those of hyaluronic acid. This polymer is completely degraded in the natural environment and within the human body, ultimately decomposing into endogenous glutamic acid without toxicity or side effects. Based on these properties, γ-PGA has been widely used in cosmetics, pharmaceuticals, health products, and hygiene products, making it a highly promising biodegradable medical polymer material.

[0006] Hyaluronic acid is a naturally occurring glycosaminoglycan widely distributed in animal connective tissue, synovial fluid, and microbial cell walls. Its molecule consists of repeating glucuronic acid and N-acetylglucosamine disaccharide units linked alternately by β-1,4 and β-1,3 glycosidic bonds, forming a linear polymer chain. Hyaluronic acid possesses extremely strong water-retention capacity, binding large amounts of water molecules to form a viscous hydrogel, imparting excellent lubrication and pressure resistance to tissues. As an important component of ECM (extracorporeal membrane oxygenation), it does not induce immune rejection and can be progressively degraded into small oligosaccharides by hyaluronidase in vivo, ultimately metabolized into carbon dioxide and water. Based on its excellent biocompatibility, biodegradability, and rheological properties, hyaluronic acid has been widely used in joint viscoelasticity repair, ophthalmic surgery, wound healing, and facial soft tissue filling, making it one of the most classic materials in modern biomedical materials. Summary of the Invention

[0007] The first objective of this application is to provide a gel matrix comprising: hyaluronic acid or a salt thereof, polyglutamic acid or a salt thereof, and agarose; wherein the hyaluronic acid or a salt thereof, polyglutamic acid or a salt thereof, and agarose are physically cross-linked to form a gel.

[0008] The hyaluronic acid or its salt is selected from one, two, or three of low molecular weight hyaluronic acid or its salt, medium molecular weight hyaluronic acid or its salt, and high molecular weight hyaluronic acid or its salt; The low molecular weight hyaluronic acid or its salt has a molecular weight of 100,000 Da or more but less than 1,000,000 Da, more preferably 200,000-900,000 Da, 300,000-800,000 Da, 400,000-700,000 Da, or 500,000-600,000 Da. Specifically, it can be 100,000 Da, 200,000 Da, 300,000 Da, 400,000 Da, 500,000 Da, 600,000 Da, 700,000 Da, 800,000 Da, 900,000 Da, or 990,000 Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The molecular weight of the medium-molecular-weight hyaluronic acid or its salt is greater than 1 million Da and less than 2 million Da, more preferably 1.1-1.9 million Da, 1.2-1.8 million Da, 1.3-1.7 million Da, 1.4-1.6 million Da, specifically 1 million Da, 1.1 million Da, 1.2 million Da, 1.3 million Da, 1.4 million Da, 1.5 million Da, 1.6 million Da, 1.7 million Da, 1.8 million Da, 1.9 million Da and 1.99 million Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The molecular weight of the high molecular weight hyaluronic acid or its salt is 2 million Da or more, more preferably 2.01-2.2 million Da, 2.01-2.4 million Da, 2.01-2.5 million Da, 2.01-2.8 million Da, or 2.01-3 million Da. Specifically, it can be 2.01 million Da, 2.2 million Da, 2.4 million Da, 2.6 million Da, 2.8 million Da, or 3 million Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The polyglutamic acid or its salt is selected from one, two, or three of low molecular weight polyglutamic acid or its salt, high molecular weight polyglutamic acid or its salt, and ultra-high molecular weight polyglutamic acid or its salt; The molecular weight of the low molecular weight polyglutamic acid or its salt is 200,000 Da or more and less than 500,000 Da, more preferably 250,000-450,000 Da and 300,000-400,000 Da, specifically 200,000 Da, 220,000 Da, 250,000 Da, 300,000 Da, 350,000 Da, 400,000 Da, 450,000 Da and 490,000 Da. The range and values ​​between the above range and specific values ​​are also included in this application. The molecular weight of the high-molecular-weight polyglutamic acid or its salt is 800,000 Da or more and less than 1,500,000 Da, more preferably 900,000-1,400,000 Da, 1,000,000-1,300,000 Da and 1,100,000-1,200,000 Da, specifically 800,000 Da, 900,000 Da, 1,000,000 Da, 1,100,000 Da, 1,200,000 Da, 1,300,000 Da, 1,400,000 Da and 1,490,000 Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The molecular weight of the ultra-high molecular weight polyglutamic acid or its salt is greater than 1.8 million Da and less than 2.5 million Da, more preferably 1.9-2.4 million Da, 2.0-2.3 million Da and 2.1-2.2 million Da, specifically 1.8 million Da, 1.9 million Da, 2 million Da, 2.1 million Da, 2.2 million Da, 2.3 million Da, 2.4 million Da and 2.49 million Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The agarose is selected from one, two, or three of low molecular weight agarose, medium molecular weight agarose, and high molecular weight agarose; The molecular weight of the low molecular weight agarose is less than 10,000 Da, more preferably 0.2-0.900 Da, 0.3-0.900 Da, 0.4-0.900 Da and 0.5-0.900 Da, specifically 0.2000 Da, 0.3000 Da, 0.4000 Da, 0.5000 Da, 0.6000 Da, 0.7000 Da, 0.8000 Da and 0.9000 Da. Ranges and values ​​between the above ranges and specific values ​​are also included in this application. The molecular weight of the medium-molecular-weight agarose is greater than 10,000 Da and less than 100,000 Da, more preferably 20,000-90,000 Da, 30,000-80,000 Da, 40,000-70,000 Da and 50,000-60,000 Da, specifically 10,000 Da, 20,000 Da, 30,000 Da, 40,000 Da, 50,000 Da, 60,000 Da, 70,000 Da, 80,000 Da, 90,000 Da and 99,000 Da. The range and values ​​between the above range and specific values ​​are also included in this application. The molecular weight of the high molecular weight agarose is 100,000 Da or more, and more preferably 110,000-120,000 Da, 120,000-130,000 Da, 130,000-140,000 Da, or 140,000-150,000 Da. Specifically, it can be 100,000 Da, 110,000 Da, 120,000 Da, 130,000 Da, or 150,000 Da. The range and values ​​between the above range and specific values ​​are also covered in this application. More preferably, the agarose is low molecular weight agarose or medium molecular weight agarose.

[0009] More preferably, the gel matrix comprises medium molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and medium molecular weight agarose, or comprises low molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and low molecular weight agarose, or comprises high molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and low molecular weight agarose, or comprises medium molecular weight hyaluronic acid or its salt, high molecular weight polyglutamic acid or its salt and medium molecular weight agarose.

[0010] More preferably, relative to 1 part by weight of hyaluronic acid or its salt, the polyglutamic acid or its salt is 0.05-1 part by weight, preferably 0.2-0.5 parts by weight, more preferably 0.5 parts by weight, and the agarose is 0.5-5 parts by weight, preferably 1-2 parts by weight, more preferably 1 part by weight.

[0011] More preferably, the hyaluronic acid or its salt, polyglutamic acid or its salt, and agarose form a gel only through physical cross-linking.

[0012] The second objective of this application is to provide a method for preparing a gel matrix, specifically, mixing agarose with water and heating until dissolved, then adding hyaluronic acid or its salt and polyglutamic acid or its salt, mixing evenly to obtain a gel, and sterilizing the gel to obtain the gel matrix, wherein the sterilization method is preferably moist heat sterilization.

[0013] A third objective of this application is to provide an application of a gel matrix in tissue filling, preferably in facial skin filling.

[0014] The fourth objective of this application is to provide a composite tissue filler comprising a bioactive material and the gel matrix.

[0015] Further, the bioactive material is either decellularized extracellular matrix or recombinant human extracellular matrix. The decellularized extracellular matrix is ​​of natural tissue origin, such as human adipose tissue, porcine dermal tissue, porcine small intestinal mucosa, and bovine dermal tissue. The recombinant human extracellular matrix refers to a recombinant human extracellular matrix formed by first expressing a single protein through genetic engineering technology, including but not limited to collagen, fibronectin, elastin, hydrin, and laminin, and then artificially mixing and compounding them. Decellularized extracellular matrix derived from porcine dermal tissue is preferred.

[0016] Furthermore, the particle size range of the bioactive material is 50-400 μm, preferably 100-300 μm.

[0017] More preferably, the bioactive material is 0.001-0.015 parts by weight, more preferably 0.002-0.015 parts by weight, and even more preferably 0.01 parts by weight, relative to 1 part by weight of the gel matrix.

[0018] The fifth objective of this application is to provide a method for preparing a composite tissue filler, wherein, Step 1: Preparation of a physically cross-linked matrix Agarose, hyaluronic acid or its salt and polyglutamic acid or its salt are mixed in a certain mass ratio. First, the agarose is mixed with water and heated until dissolved. Then, hyaluronic acid or its salt and polyglutamic acid or its salt are added, stirred evenly, and then subjected to moist heat sterilization to obtain a gel matrix. Step 2: Preparation of composite tissue filler The bioactive material was pulverized and homogenized with water to obtain a specific amount of bioactive material slurry. This slurry was then mixed with the gel matrix obtained in step one under sterile conditions to obtain a composite tissue filler. Further, in step two, the specific amount of bioactive material slurry refers to a bioactive material slurry with a mass fraction of 1%-2%, more preferably 2%; the mass ratio of the specific amount of bioactive material slurry to the gel matrix is ​​(0.1-0.75):1, more preferably 0.5:1; Furthermore, the homogenization refers to a homogenization speed of 6000-10000 rpm and a homogenization time of 3-8 min.

[0019] The sixth objective of this application is to provide an application of a composite tissue filler in tissue filling, preferably in facial skin filling.

[0020] The beneficial effects of this application are: The gel matrix provided in this application is a physically cross-linked gel formed by combining the characteristics of hyaluronic acid or its salts, polyglutamic acid or its salts, and agarose. It avoids the use of chemical cross-linking agents, suspending certain bioactive materials such as decellularized dermal matrix, allowing for smooth injection without needle clogging, and exhibiting slow degradation. Physical cross-linking refers to the formation of a gel through physical forces such as electrostatic interactions, ionic interactions, hydrogen bonding, and chain entanglement, avoiding the use of chemical cross-linking agents. The physical cross-linking method used in this application mainly utilizes the electrostatic interactions and hydrogen bonding between the three polymers: agarose, polyglutamic acid or its salts, and hyaluronic acid or its salts, to form a physically cross-linked gel. The semi-rigid structure of hyaluronic acid gel and the flexible structure of polyglutamic acid solve the problems of agarose's brittleness, hard texture, and post-injection dryness. Simultaneously, the combination of hyaluronic acid and polyglutamic acid improves the moisturizing properties of the composite gel, inhibits the degradation of hyaluronic acid, and prolongs the degradation time. Compared with comparative examples 1.1, 1.2 and 1.3, the gel matrix provided in this application has both slow degradation properties and a certain suspension capacity, does not use cross-linking agents, and has good injection performance.

[0021] The composite tissue filler provided in this application comprises a gel matrix and bioactive materials. It utilizes the bioactive material (decellularized dermal matrix) to create an injectable "dermal regeneration scaffold," offering better support, lower cost, slower degradation, and longer-lasting effects compared to enzymatically hydrolyzed ECM or dECM. This composite tissue filler offers advantages such as smooth injection without needle clogging, no post-injection swelling, high post-operative moisturization, soft and natural appearance, reduced inflammation, and good tissue integration. Furthermore, the introduction of bioactive materials like decellularized dermal matrix into the gel matrix further enables targeted regeneration and promotes healthy tissue microenvironment growth. Compared to Comparative Examples 2.1 and 2.2, the filler provided in this application exhibits slow degradation, does not use cross-linking agents, and provides excellent injectability. Attached Figure Description

[0022] Figure 1 Appearance of the gel matrix in Example 1.1 (1A) and Comparative Example 1.3 (1B); Figure 2 Example 2.3 (2A) and Comparative Example 2.2 (2B) Appearance of composite tissue filler. Detailed Implementation

[0023] The present application will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0024] I. Main Materials The sources of the main materials involved in the embodiments and comparative examples are shown in the table below:

[0025] Microparticle decellularized dermal matrix (mADM) was prepared by referring to: LIU C, SUN J. A porcineacellular dermal matrix induces human fibroblasts to secrete hyaluronic acid by activating JAK2 / STAT3 signalling[J]. RSC Advances, 2020, 10(32):18959-18969. Porcine dermal tissue was decellularized to form dECM, and then pulverized to 100-300μm to obtain microparticle decellularized dermal matrix (mADM).

[0026] II. Testing Methods The gels obtained in the examples and comparative examples were subjected to performance tests, including rheological property tests, degradation rate, extrusion force, dynamic viscosity tests, and suspension effect tests, as detailed below: Rheological performance testing: The elasticity and viscous modulus of the gel matrix and composite tissue filler were measured using a rotational rheometer (100 mm gap, 1% deformation, frequency range 0.1 Hz ~ 10 Hz) at 25 ℃. Degradation rate: After lyophilizing the composite hydrogels of different concentrations, the samples were weighed (G1) and placed in centrifuge tubes containing PBS. The tubes were then kept at a constant temperature of 37°C, with the PBS replaced weekly. After 1, 2, 3, 4, 5, 6, 7, and 8 weeks, the PBS in the centrifuge tubes was removed, the liquid on the surface of the hydrogels was blotted dry with filter paper, and the samples were lyophilized and weighed (G2). The in vitro degradation changes and degradation rate of the composite hydrogels were calculated using the formula (G1-G2 / G1)*100%.

[0027] Pushing force: For gel matrix or filler tests, attach a 30G injection needle and push the injection handle at a speed of 30 mm / min using a universal testing machine. Record the pressure. Test each sample three times and calculate the average value. Maximum and minimum pushing force difference = maximum pushing force - minimum pushing force.

[0028] Dynamic viscosity test: Dynamic viscosity η was tested using a rotational rheometer at a test temperature of 25℃ and a frequency of 1Hz.

[0029] Suspension effect test: 5% mADM slurry (preparation method: the mass ratio of mADM to water is 1:19, the two are homogenized at 7000 rpm for 5 min) was mixed with the gel matrix to be tested at a weight ratio of 1:1, and the suspension was tested by centrifugation at 3000 r / min for 10 min.

[0030] Preparation Examples A method for preparing a composite tissue filler includes the following steps: Step 1: Preparation of the gel matrix Medical-grade agarose, sodium hyaluronate, and sodium polyglutamate were mixed in a mass ratio of 1:1:0.5 to prepare solutions with concentrations of 1%, 1%, and 0.5%, respectively. The specific steps were as follows: First, 1g of medical-grade agarose was mixed with 97.5g of water and heated to 80-100℃ until completely dissolved and bubbling. Then, the mixture was cooled to 50-60℃ and 1g of sodium hyaluronate and 0.5g of sodium polyglutamate were added and stirred evenly. The mixed gel was then subjected to moist heat sterilization (121℃, 20min) to obtain the gel matrix.

[0031] Step 2: Preparation of composite tissue filler mADM and water were homogenized together at room temperature (mADM mass fraction of 1%-2%, homogenization speed of 6000-10000 rpm, time of 3-8 min) to obtain mADM slurry. The mADM slurry was then mixed with the gel matrix obtained in step one under sterile conditions (mADM slurry to gel matrix mass ratio of (0.1-1):1) to obtain a composite tissue filler.

[0032] Example 1: Preparation of Gel Matrix In Table 1, "Low HA" indicates low molecular weight sodium hyaluronate with a molecular weight of 520,000 Da, "Medium HA" indicates medium molecular weight sodium hyaluronate with a molecular weight of 1,390,000 Da, and "High HA" indicates high molecular weight sodium hyaluronate with a molecular weight of 2,230,000 Da; "Low PGA" indicates low molecular weight sodium polyglutamate with a molecular weight of 216,000 Da, "High PGA" indicates high molecular weight sodium polyglutamate with a molecular weight of 1,040,000 Da, and "Ultra-High PGA" indicates ultra-high molecular weight sodium polyglutamate with a molecular weight of 2,030,000 Da; "Low AG" indicates low molecular weight agarose with a molecular weight of 8,000 Da, "Medium AG" indicates medium molecular weight agarose with a molecular weight of 52,000 Da, and "High AG" indicates high molecular weight agarose with a molecular weight of 120,000 Da.

[0033] Following step one in the preparation examples, and according to the content and ratio of each component in Table 1, Examples 1.1-1.10 and Comparative Examples 1.1-1.2 were formed. Furthermore, based on the aforementioned test methods, the elastic modulus, viscous modulus, pushing force, difference between maximum and minimum pushing force, degradation rate, and suspension effect were tested, and the results are shown in Table 1. The unit of elastic modulus is G' (kPa); the unit of viscous modulus is G" (kPa).

[0034] The above abbreviations also apply to other embodiments.

[0035] The degradation rate in Table 1 refers to the degradation rate at week 8, and the unit is %.

[0036] The gel matrices obtained in Examples 1.1-1.10 and Comparative Examples 1.1-1.2, and the crosslinked gel matrix of Comparative Example 1.3 were prepared according to claim 3 and Example 3 of CN114949359A. The specific steps are as follows: 1g of HA, 0.5g of low PGA, 1.0g of AG, 25g of 1M NaOH solution were added, and then 6g of crosslinking agent BDDE (concentration of 60%) was added. Crosslinking was carried out at room temperature for 15h, and then the crosslinking agent was removed by soaking in purified water to obtain crosslinked gel. All products were tested according to the sterility testing methods in the Chinese Pharmacopoeia and were found to be sterile and qualified.

[0037] Table 1. Composition and test results of each component in Examples 1.1-1.9 and Comparative Examples 1.1-1.2.

[0038] From an external perspective, Example 1.1 ( Figure 1 A)-1.10 and Comparative Examples 1.1-1.2 are both transparent gels, while Comparative Example 1.3 ( Figure 1 B) is a micropermeable gel, and the gel contains air bubbles.

[0039] This application aims to obtain a gel that is slow-degradable, possesses a certain suspending ability, does not use a cross-linking agent, and provides good injection performance. Slow degradation refers to a lower degradation rate compared to commercially available cross-linked sodium hyaluronate gels (such as Juvederm Voluma, which, according to the degradation rate test method described in this application, achieved a degradation rate of 51.6% in week 4); certain suspending ability refers to no sedimentation or partial sedimentation shown in suspension effect tests; and good injection performance refers to moderate pushing force and small fluctuations in pushing force.

[0040] As shown in Table 1, the pushing force variations in Comparative Examples 1.1 and 1.2 are very large, specifically the difference between the maximum and minimum pushing force is very large (2.312 and 4.321, respectively), indicating an uneven pushing force and a jerky injection feel, which is significantly higher than that of Examples 1.1-1.10 (0.219-1.303). The reason for this may be that Comparative Example 1.1 lacks the support of the flexible segments of sodium polyglutamate, resulting in a less dense three-dimensional network and larger pores, thus leading to a large variation in pushing force. Similarly, Comparative Example 1.2 lacks the semi-rigid structure of sodium hyaluronate bridging the rigid framework and filling the pores, also resulting in a large variation in pushing force. In the embodiments of this application, by adding both hyaluronic acid and sodium polyglutamate to the agarose base, the viscosity (G") and shear resistance of the gel are increased, resulting in a smoother injection feel without jerking.

[0041] Although the difference in pushing force between Examples 1.2 and 1.4 is relatively large, the reason may be that the addition of high AG increases the brittleness of the product, and the uniformity of pushing force is slightly worse than that of other examples, but it is still significantly better than Comparative Examples 1.1 and 1.2.

[0042] As shown in Table 1, although Comparative Example 1.3 has a difference between the maximum and minimum injection force comparable to that of the embodiments of this application, the embodiments of this application have the advantage of not using a crosslinking agent compared to Comparative Example 1.3.

[0043] In summary, Examples 1.1-1.10 of this application, compared with Comparative Examples 1.1, 1.2 and 1.3, have both slow degradation properties and a certain suspension ability, do not use crosslinking agents, and have good injection performance.

[0044] In the gel matrix provided in this application, agarose has a rigid structure, which provides mechanical strength and thermal stability to the gel matrix. After cooling and gelling through hydrogen bonding, it can act as a rigid reinforcing phase, improving the storage modulus (G') and deformation resistance of the gel matrix. Sodium hyaluronate has a semi-rigid structure, while sodium polyglutamate has a flexible structure. Sodium hyaluronate and sodium polyglutamate can, to some extent, disrupt the rigid structure of agarose in the gel matrix. By relying on molecular chain entanglement, they can improve the water retention and shear resistance (G") of the gel matrix. Furthermore, the synergistic structure of sodium hyaluronate and sodium polyglutamate in the matrix increases the uniformity of the gel matrix, making the extrusion force more balanced, the extrusion process more stable and gentle, and easier to inject. Moreover, sodium polyglutamate in the gel matrix can, to some extent, slow down the degradation rate of the gel matrix.

[0045] Example 2 According to step two of the preparation example, 2g of mADM and 98g of water were mixed and homogenized (7000rpm for 5min) to obtain 100g of extracellular matrix solution; 20g of gel matrix prepared in step one was further taken out and magnetically stirred with a quantitative amount of extracellular matrix solution according to Table 2 (200rpm for 15min). In Table 2, Examples 2.1-2.5 all used the gel matrix prepared in Example 1.1; Comparative Example 2.1 used the gel matrix prepared in Comparative Example 1.1.

[0046] Comparative Example 2.2 The filler was prepared according to claims 3 and 4 of CN114949359A and Example 3, and the specific steps are as follows: (1) Preparation of cross-linked gel matrix: 1g of medium HA, 0.5g of low PGA, 1.0g of medium AG, 25g of 1M NaOH solution, and then 6g of cross-linking agent BDDE (concentration of 60%) were added. Cross-linking was carried out at room temperature for 15h, and then the cross-linking agent was removed by soaking in purified water to obtain cross-linked gel; (2) Preparation of non-crosslinked gel matrix: 1g of medium HA, 0.5g of low PGA and 1.0g of medium AG were added to 25g of purified water to obtain a non-crosslinked gel; (3) Mix 10g of 2% mADM slurry with 20g of mixed gel (10g each of cross-linked gel and non-cross-linked gel): Mix the cross-linked gel and non-cross-linked gel by stirring at room temperature in equal weight (200rpm, 15min), and mix 20g of mixed gel with 10g of 2% mADM slurry by magnetic stirring (200rpm, 15min) to obtain a filler containing extracellular matrix.

[0047] Based on the aforementioned test methods, dynamic viscosity, elastic modulus, viscous modulus, pushing force, difference between maximum and minimum pushing force, and degradation rate were tested respectively, and the results are shown in Table 2.

[0048] Table 2. Composition and test results of each component in Examples 2.1-2.5 and Comparative Examples 2.1-2.2.

[0049] From an external perspective, Examples 2.1, 2.2, and 2.3 ( Figure 2 A), 2.4 and 2.5, and Comparative Example 2.1 are all microtransparent gels, while Comparative Example 2.2 ( Figure 2 B) is an impermeable gel. The gel obtained in Comparative Example 2.2 has heavy particles, and the mixing of non-crosslinked and crosslinked gels is not uniform. Although the viscosity is high, it cannot form a rigid structure, and the injection force is uneven.

[0050] This application also aims to obtain a filler that can both slowly degrade, avoid the use of cross-linking agents, and provide good injection performance. Slow degradation refers to a lower degradation rate compared to commercially available cross-linked sodium hyaluronate gels (such as Juvederm Voluma, whose degradation rate, measured according to the degradation rate test method described in this application, reaches 51.6% in 4 weeks); good injection performance refers to moderate pushing force and small fluctuations in pushing force.

[0051] As shown in Table 2, the ratio of extracellular matrix to gel matrix in Examples 2.3, 2.1, and 2.2 was 0.5:1. The difference between the maximum and minimum pushing forces in Comparative Examples 2.1 and 2.2 was 7.489 and 9.373, respectively, significantly higher than that in Example 2.3 (3.902). Therefore, the filler of this application is also significantly superior to Comparative Examples 2.1 and 2.2.

[0052] Based on the above analysis, the embodiments of this application, compared with Comparative Examples 2.1 and 2.2, can both slowly degrade, not use crosslinking agents, and provide fillers with good injection performance.

[0053] Generally, the greater the pushing force, the greater the resistance to product injection, and prolonged injection can lead to hand fatigue. When the pushing force exceeds 20N, the injection flow rate fluctuates greatly, increasing the risk of subcutaneous nodule formation. Considering that this application is a particulate gel, the 30G syringe is prone to clogging, and excessive pushing force can damage the gel and ECM fiber structure. Therefore, the reasonable range of the filling force should not exceed 20N (30G). Based on this, the weight ratio of 2% mADM slurry to gel matrix in this application should be less than or equal to 0.75:1.

[0054] Example 3 The fillers prepared in Example 2.3 (experimental group) and Comparative Example 2.1 (control group) of this application were injected into New Zealand rabbits (purchased from Shaanxi Junxing Biotechnology Co., Ltd., and raised at Xi'an Guolian Quality Inspection Technology Co., Ltd., 6 females, weighing 2.0kg-3.0kg). 200μL was injected intradermally at each point. The experimental group was injected on the left side, and the control group was injected on the right side. The in vitro dimensions were measured using a digital caliper at 1 week, 4 weeks, 12 weeks, 26 weeks, and 52 weeks after injection. The implant volume was measured and calculated (the measurement method mentioned for the implant is referenced in: Liu X, Niu H, Shi M, et al. Objective Noninvasive Measurement of the Volumizing Effect of a Dermal Filler: An In Vivo Study, Aesthetic Plast Surg. 2024,48(19):4024-4030) to further evaluate the degradation of the implant. At the same time, any abnormalities such as bleeding and swelling in the animals were observed during the experiment. The volume test and calculation results of the implant are shown in Table 3. The volume retention rate of the implant is also shown in Table 3, and its calculation formula is: Volume V at each time point t / Initial volume V0*100%.

[0055] During the experiment, no abnormalities such as bleeding or swelling were observed in either the experimental or control groups of rabbits.

[0056] Table 3. Volume change and volume retention rate of the fillers prepared in Example 2.3 and Comparative Example 2.1 after intra-rabbit injection.

[0057] According to the test results in Table 3, the filler prepared in this application (Example 2.3) can achieve slow absorption and gradient degradation of bioactive components compared with Comparative Example 2.1.

[0058] One week after the filler was injected into the rabbits, the volume first increased and then decreased. The reason for this was that the sodium hyaluronate absorbed water and swelled in the early stage, causing the filler to increase in volume. In the later stage, as the filler gradually degraded, its volume gradually decreased.

[0059] The volume retention rate index revealed that in weeks 4, 12, 26, and 52, the volume retention rates of both Example 2.3 and Comparative Example 2.1 showed a decreasing trend, with Example 2.3 exhibiting a slower rate of decrease compared to Comparative Example 2.1. At each time point, the volume retention rate of Example 2.3 was higher than that of Comparative Example 2.1, and the difference in volume retention rates increased over time: in week 1, the volume retention rate of Example 2.3 was 0.9% higher than that of Comparative Example 2.1; in week 4, it was 6.35% higher; in week 12, it was 7.54% higher; in week 26, it was 10.86% higher; and in week 52, it was 12.47% higher. This indicates that the filler prepared using the gel matrix of this application degrades more slowly and its effective effect is more lasting. The reason for this difference lies in the gel matrix used in Example 2.3, which is a physically cross-linked gel formed from hyaluronic acid, sodium polyglutamate, and agarose, while the gel matrix used in Comparative Example 2.1 is a gel formed from hyaluronic acid and agarose. The physically cross-linked gel formed by the three components in Example 2.3 utilizes the rigid double helix structure of agarose to provide a stable, enzyme-resistant support framework, reducing network pore size and preventing the invasion of body fluids and enzymes. The semi-rigid chain structure of sodium hyaluronate provides lateral bridging of the rigid framework, filling pores and perfecting the three-dimensional network. The linear long chain structure of sodium polyglutamate provides numerous hydrogen bond binding sites, entangled and locking the entire system, further enhancing network density. The three components physically intertwine to form a high-density hydrogen-bonded interpenetrating network, which, through the triple effects of shielding enzyme cleavage sites, inhibiting swelling diffusion, and gradient hydrogen bond dissociation, collectively reduces the rate of hydrolysis and enzymatic degradation, achieving slow absorption and degradation within the gel.

[0060] The filler provided in this application comprises a physically cross-linked gel formed from hyaluronic acid, sodium polyglutamate, and agarose. Furthermore, the filler also contains mADM, enabling it to both suspend bioactive components such as the extracellular matrix for targeted regeneration and to be smoothly injected in suspension without clogging the needle. This application avoids the use of chemical cross-linking agents. The filler provided in this application exhibits good injectability, does not cause swelling, and provides excellent postoperative hydration, a soft and natural appearance, reduced inflammation, and good tissue integration.

[0061] The ratio of 2% mADM slurry to gel matrix used in this embodiment is limited to animal experiments only. In practical applications, the ratio of bioactive materials and gel matrix can be flexibly adjusted according to different requirements such as injection needle specifications, injection tissue layers, and injection depth.

[0062] The above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A gel matrix comprising: Hyaluronic acid or its salt, polyglutamic acid or its salt, and agarose; wherein the hyaluronic acid or its salt, polyglutamic acid or its salt, and agarose form a gel through physical cross-linking.

2. The gel matrix according to claim 1, wherein, The hyaluronic acid or its salt is selected from one, two, or three of the following: low molecular weight hyaluronic acid or its salt, medium molecular weight hyaluronic acid or its salt, and high molecular weight hyaluronic acid or its salt; The polyglutamic acid or its salt is selected from one, two, or three of low molecular weight polyglutamic acid or its salt, high molecular weight polyglutamic acid or its salt, and ultra-high molecular weight polyglutamic acid or its salt; The agarose is selected from one, two, or three of low molecular weight agarose, medium molecular weight agarose, and high molecular weight agarose; The low molecular weight hyaluronic acid or its salt has a molecular weight of 100,000 Da or more but less than 1,000,000 Da; the medium molecular weight hyaluronic acid or its salt has a molecular weight of 1,000,000 Da or more but less than 2,000,000 Da; and the high molecular weight hyaluronic acid or its salt has a molecular weight of 2,000,000 Da or more. The low molecular weight polyglutamic acid or its salt has a molecular weight of 200,000 Da or more and less than 500,000 Da; the high molecular weight polyglutamic acid or its salt has a molecular weight of 800,000 Da or more and less than 1,500,000 Da; the ultra-high molecular weight polyglutamic acid or its salt has a molecular weight of 1,800,000 Da or more and less than 2,500,000 Da. The low molecular weight agarose has a molecular weight of less than 10,000 Da, the medium molecular weight agarose has a molecular weight of more than 10,000 Da but less than 100,000 Da, and the high molecular weight agarose has a molecular weight of more than 100,000 Da; Preferably, the agarose is low molecular weight agarose or medium molecular weight agarose; More preferably, the gel matrix comprises medium molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and medium molecular weight agarose, or comprises low molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and low molecular weight agarose, or comprises high molecular weight hyaluronic acid or its salt, low molecular weight polyglutamic acid or its salt and low molecular weight agarose, or comprises medium molecular weight hyaluronic acid or its salt, high molecular weight polyglutamic acid or its salt and medium molecular weight agarose; More preferably, relative to 1 part by weight of hyaluronic acid or its salt, the polyglutamic acid or its salt is 0.05-1 part by weight, preferably 0.2-0.5 parts by weight, more preferably 0.5 parts by weight, and the agarose is 0.5-5 parts by weight, preferably 1-2 parts by weight, more preferably 1 part by weight.

3. The gel matrix according to claim 1 or 2, wherein the hyaluronic acid or its salt, polyglutamic acid or its salt, and agarose form a gel only through physical cross-linking.

4. A method for preparing a gel matrix according to any one of claims 1-3, wherein, The agarose is mixed with water and heated until dissolved. Then, the hyaluronic acid or its salt and polyglutamic acid or its salt are added and mixed evenly to obtain a gel. The gel is then sterilized to obtain the gel matrix. The preferred sterilization method is moist heat sterilization.

5. The application of the gel matrix according to any one of claims 1-4 in tissue filling, preferably in facial skin filling.

6. A composite tissue filler, wherein, The composite tissue filler comprises a bioactive material and a gel matrix as described in any one of claims 1-5. More preferably, the bioactive material comprises 0.001-0.015 parts by weight, more preferably 0.002-0.015 parts by weight, and even more preferably 0.01 parts by weight, relative to 1 part by weight of the gel matrix.

7. The composite tissue filler according to claim 6, wherein, The bioactive material is either decellularized extracellular matrix or recombinant human extracellular matrix. The decellularized extracellular matrix is ​​of natural tissue origin, such as human adipose tissue, porcine dermal tissue, porcine small intestinal mucosa, and bovine dermal tissue. The recombinant human extracellular matrix is ​​prepared by first expressing a single protein separately through genetic engineering technology and then artificially mixing and compounding it. Decellularized extracellular matrix derived from porcine dermal tissue is preferred.

8. The composite tissue filler according to any one of claims 6-7, wherein, The particle size range of the bioactive material is 50-400 μm, preferably 100-300 μm.

9. A method for preparing the composite tissue filler according to any one of claims 6-8, wherein, The bioactive material is pulverized and homogenized with water to obtain a specific amount of bioactive material slurry, which is then mixed with the gel matrix of any one of claims 1-5 under sterile conditions to obtain the composite tissue filler; preferably, the specific amount of bioactive material slurry refers to a bioactive material slurry with a mass fraction of 1%-2%, more preferably 2%; the mass ratio of the specific amount of bioactive material slurry to the gel matrix is ​​(0.1-0.75):1, more preferably 0.5:

1.

10. The application of the composite tissue filler according to any one of claims 6-9 in tissue filling, preferably in facial skin filling.

Citation Information

Patent Citations

  • Acellular matrix particle filler and preparation method thereof

    CN114949359A

  • Injection filling material and preparation and application thereof

    CN116212112A